Sosialisasi Perkwaninan di Bawah Umur dan Akibatnya bagi Remaja Masjid dan Karang Taruna di Kecamatan Jamapolo Kabupaten Karanganyar - khoirunnissa, izzun; Hidayat, M. Yunan; Syamsuddin, Syamsuddin; Sugiyat, Sugiyat; Azhar, Syihab (Universitas Muhammadiyah Enrekang, 2024)
Marriage is a living association between a man and a woman which is formally confirmed by law (juridical) and mostly religious. Marriage is a legal relationship between a man and a woman for a long time. One of the conditions for a valid marriage is the age limit of the bride and groom. According to Law no. 1 of 1974 the age limit states that marriage is only permitted if the man has reached the age of 19 and the woman has reached the age of 16, unless a dispensation is obtained from a judicial institution with strong reasons. UU no. 1 of 1974 was later amended by Law no. 16 of 2019 regarding the marriage age limit, which was originally a minimum age of 19 years for men and 16 years for women, changed to a minimum of 19 years for men and 19 years for women. In Indonesia, underage marriage is still a national phenomenon. Cultural and economic factors still dominate and become factors that influence the pattern of life in society. because the impact is very complex, both for those concerned including the child to be born. the age of the child already has offspring (children).